Multispecies Swarm Electrification for Rural Areas of the Developing World - George Kyriakarakos; George Papadakis (Applied Sciences, 2019)
Today, 992 million people still do not have access to electricity globally. Most live in rural areas of the developing world. In 2018, the electrification rate for sub-Saharan Africa was only 27%. Furthermore, off-grid systems are projected to provide 65% of the newly electrified population in sub-Saharan Africa. Current estimations show that the average connection cost per technology in rural areas of sub-Saharan Africa is 2000−3000 USD for grid extension, 500−1200 USD for a microgrid solution, and 150−500 USD for a solar home system. The most recent studies for real-world microgrids installed in sub-Saharan Africa show that the average split of capital expenditure (CAPEX) spending on distribution versus generation in microgrids is at 50%/50%. This is the result of the significant cost reduction of photovoltaics, batteries, and power electronics, in comparison with the practically stable unchanged cost of poles and cables. Even if the business model is chosen by the investor—usually a pay-as-you-go implementation—there is still the difficult decision to make on whether to go for a microgrid or solar home systems. Taking inspiration from multispecies swarms, a Multispecies Swarm Electrification approach is developed that is able to meet the real-world needs of the developing world in terms of rural electrification.